An experimental investigation of the thermal performance of a building solar shading device. (March 2020) - Evangelisti, Luca; Guattari, Claudia; Asdrubali, Francesco; de Lieto Vollaro, Roberto
Abstract: Understanding the thermal performance of building envelopes and of their components is a critical issue under energy saving and sustainability points of view. High performance buildings are commonly characterized by passive solutions able to avoid overheating during summertime or to take advantage of solar radiation during wintertime. This study provides an experimental investigation of the thermal performance of a refurbished building which was re-designed aiming at high performance from both an active and passive point of view. The building envelope was investigated, examining the influence of the external shading devices by means of in-situ measurements and introducing an index for the evaluation of the shielding system efficiency. The index was tested by means of numerical simulations and measured data, providing information about the efficiency of the solar shading device in terms of glazing external surface temperature reduction. It was found that the shielding system allows to achieve a reduction in terms of incoming thermal energy equal to 38.7% during summertime. The index could be used both for opaque and transparent building components covered by a shading device, independently by the shape of the shading system or by the thermal performance of the component. The index could be therefore useful for both solar shading devices producers and for practitioners for preliminary design evaluations. Highlights: Influence of the external shading devices by means of in-situ measurements. Suggestion of a new index for evaluating the efficiency of the shielding system. Preliminary application and validation of the suggested index.